Outlining the Orientation Toward Socially Relevant Issues in Competitive R&D Funding Instruments - Spinello, Andrea Orazio; Reale, Emanuela; Zinilli, Antonio (Frontiers in Research Metrics and Analytics, 2021)
While project-based funding in public R&D investments has grown in importance in all European countries over the last two decades, there is widespread concern among decision makers about the actual orientation of project funding instruments to promote innovation and well-being. The capability of public R&D investment to improve the quality of citizens' lives implies the pursuit of 'relevant' social objectives related to existing and/or emerging problems affecting individuals' lives and society. Particularly, when referring to project-funded research, the question of ‘relevance' in research objectives recalls the never-ending debate over how to translate policymakers' request for producing value from public investments in research activities into ‘usable results'. The manuscript explores, using existing recent data collected at European level on government R&D funding, the portfolio of research project funding policy instruments of various public research funding organizations (RFOs) in order to shed light on how and to what extent it is oriented to address socially relevant topics. The authors examine the characterization of the single project funding instruments, which are intended to incorporate the motivations and targeted goals of public action, and the RFOs that manage them. In particular, they assume that, beyond the declared objectives, the actual orientation of funding instruments is influenced by specific features related to their implementation operated by the RFOs, such as those related to the process for selecting beneficiaries, thus evaluation criteria and their importance, and the composition of evaluation panels.